ANALISIS KARAKTERISTIK WIRAUSAHA DAN KOMPETENSI KEWIRAUSAHAAN SEBAGAI PENENTU KINERJA USAHA KECIL MENENGAH DI PERKAMPUNGAN WISATA BUDAYA BETAWI SETU BABAKAN JAKARTA - Ahmad Nurdin Hasibuan; Tagor Rembey; Reny Andriyanty (Program Studi Manajemen, Fakultas Ekonomi, IBI-K57, 2020)
This study aims to analyze the influence of entrepreneurial characteristics, business adaptation, and management competence on the business performance of Setu Babakan SMEs in South Jakarta. The data gathered from food and beverage small business holder. The analysis have analyzed by structural equation model. The research resulted that all exogenous latent variables are significantly influence the endogenous latent variable.